Pendayagunaan Wakaf Sebagai Pengembangan Sosial-Ekonomi Masyarakat (Analisis Wakaf Sebagai tanggung Jawab Sosial Pada Organisasi Islam) - Sri Noor Mustaqimatul Hidayah (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2023)
Involvement in the practice of social responsibility is currently seen as important for Islamiciorganizations. The potential use of waqfias a sourceiof funding forisuch practices hasinot been explored much. The purpose ofithis studyiis to provideievidence of the practice of utilizing waqf as a social responsibility of Islamic organizations. Theiresults of the study revealithat for the main program of social responsibility of Islamic organizations through the utilization of waqf, it can be carried out within the organization, while the programs considered in the utilization of waqf are focused on communityiissues. Waqf is seen as an alternativeithat can be used by Islamic organizations to help overcome social problems in society. However, there are problems that need to be addressed regarding the practice of waqf in Islamic organizations. So that further research is needed on waqf utilization reform.